2010
DOI: 10.1007/s12687-010-0016-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of hemoglobinopathies, G6PD deficiency, and ABO and Rhesus blood groups in two isolates of a primitive Kharia Tribe in Sundargarh District of Northwestern Orissa, India

Abstract: Tribal communities constitute about 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Numerous studies were reported at the context of disease epidemiology and genetics, upon various indian tribal communities, who are highly isolated both demographically and topogra phically, from the mainstream indian populations [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies were reported at the context of disease epidemiology and genetics, upon various indian tribal communities, who are highly isolated both demographically and topogra phically, from the mainstream indian populations [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…India is a large country with numerous ethnic groups wherin SCD is prevalent in numerous ethnic groups, in India. The high prevalence of sickle cell in several distinct groups in India has been the subject of extensive population based studies . Among the major ethnic groups with a high burden of SCD are autochthonous tribal peoples known as scheduled tribes or Adivasis.…”
Section: Introductionmentioning
confidence: 99%
“…The scheduled tribes consist of over 645 distinct ethnic groups consisting of over 84 million individuals representing 8% of India's population . Differences in ethnic origins, genetic background, and migration histories of these endogamous tribes, who serve as genetic isolates may explain the variation in the sickle cell trait carrier frequency of 10–33% in these populations . In many tribal communities, patients with SCD do not receive comprehensive care for SCD due to the lack of access to health care, socioeconomic deprivation, and geographical and cultural isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the strong selective effect of malaria resistance includes the high frequency of a number of detrimental hemato-genetic diseases (including the different hemoglobinopathies, thalassemias, and red cell enzymopathy), caused by the effects of these malaria resistance variants. In view of this pathetic scenario, it is justifiable that population genetics could be useful to determine the amount and pattern of natural selection in human population isolates [5][6][7][8][9][10][11][12].…”
Section: Cardinal Malaria Situationmentioning
confidence: 99%